EL ANÁLISIS DE ERRORES DEL LEÍSMO Y LAÍSMO EN EL PAPEL DIDÁCTICO PARA LOS ALUMNOS DEL DEPARTAMENTO ESPAÑOLEN LA FACULTAD DE LENGUAS EN IRAK Search Summary: The analysis of the mistakes of the personal pronouns in effect replaces him in the (Journal of the College of Languages (JCL), 2014)
During the educational practices in the Spanish department at the Faculty of Languages ​​, University of Baghdad , we noticed that the personal pronouns in effect replaced by the direct and indirect characterized hardly be expressed , and the difficulty of her education.Rationale: I chose this topic because the personal pronouns differ between the Spanish language and the Arabic language. We believe that this study may be useful not only for language teachers, but also for students, because it can contribute to a greater awareness of and correct weaknesses.Objectives: To apply the model from which to address the problems in the use of personal pronouns Spanish , and the difference between effect of direct and indirect reflectivity and pronouns , and how to address this issue for the students.Action Plan: The main objective is not to analyze the phenomenon of private grammatical, but to create a map of the errors repeated for learners to have, at the grammar, and classified according to the level of difficulty and the degree of appearance.